PEMBERDAYAAN IBU PKK MELALUI PELATIHAN PEMBUATAN ECO ENZYME DAN ABON CABAI RAWIT DI DESA MANUNGGAL KARYA KECAMATAN RANDANGAN KABUPATEN POHUWATO - Asmuliani R, Asmuliani R; Maner, Muh Arsyad; Bulotio, Nur Fitriyanti; Pertiwi, Erse Drawana; Wahyudi, Wahyudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The aim of this activity is to ensure that the PKK mothers of Manunggal Karya Village are able to improve the community's skill level through training in making Eco Enzyme and knowing how to make Chili Floss so as to be able to reduce inflation. The first stage involved socialization, which focused on the benefits of eco-enzymes and shredded cayenne pepper. The second and third stages involved training and technology implementation, specifically training on the production of eco-enzymes and shredded cayenne pepper. The 4th stage of mentoring is assisting the PKK mothers' group in making eco enzymes and chili floss. Stage 5: Evaluation using Kirkpatrick. The results of this activity are that the PKK Mother Partners of Manunggal Karya Village know and understand the benefits and methods of making eco enzymes and chili floss so that they can improve the welfare of families, especially PKK mothers of Manunggal Karya Village.